T2* weighted placental MRI in relation to placental histology and birth weight. (October 2021) - Sinding, Marianne; Sørensen, Anne; Hansen, Ditte N.; Peters, David A.; Frøkjær, Jens B.; Petersen, Astrid C.
Abstract: Introduction: Placental dysfunction may be found among normal birth weight (BW) pregnancies, as indicated by abnormal histological findings in postnatal placental examination in some of these pregnancies. T2* weighted placental MRI provides non-invasive information on placental oxygenation and thereby placental function. The aim of this study was to investigate the correlation between placental T2*, BW and placental histology. Methods: A total of 63 pregnant women underwent T2* weighted placental MRI at 15–40 week's gestation and a standardized placental histological examination (PHE). Abnormal PHE was defined by vascular malperfusion according to the Amsterdam workshop consensus. The correlation between PHE, BW z-score and T2* z-score was analyzed by logistic regression. Results: Abnormal PHE was revealed in 28 pregnancies. Multiple logistic regression revealed a significant correlation between abnormal PHE and T2* z-score (OR = 0.34, p = 0.008), whereas BW z-score did not add significantly to the correlation of placental histology (OR = 0.52, p = 0.115). In BW z-score≥0, PHE was normal in 100% of pregnancies. In BW z-score ≤ −2, PHE was abnormal in 89% of pregnancies. In intermediate BW (z-score between −2 and 0), PPE was abnormal in 35% of pregnancies. In this intermediate group, placental T2* z-score was reduced (−1.52 ± 1.22 (mean SD)) when compared to normal PHE pregnancies (−0.28 ± 1.17), p = 0.006. Discussion: This study demonstrates a correlation between abnormal placental histology and low placental T2* value regardless of fetal size. This indicates that T2* provides information of placental function in vivo even when fetal size is normal. This finding highlights that fetal size alone is not a valid marker of placental dysfunction. Highlights: Placental histology may reveal placental dysfunction regardless of neonatal size. Placental dysfunction can be depicted in vivo using T2* weighted MRI. Low T2* may identify placental dysfunction among apparently normal weight fetuses.